Forced migration in the South Asian region : displacement, human rights, and conflict resolution - Mishra, Omprakash; Jadavpur University. Centre for Refugee Studies; Brookings-SAIS Project on Internal Displacement (Kolkata : Centre for Refugee Studies, Jadavpur University, 2004)
Contributed seminar articles
Includes bibliographical references and index
Keywords: Forced migration -- South Asia -- Congresses; Refugees -- South Asia -- Congresses; South Asains -- Relocation -- Congresses; Human rights -- South Asia -- Congresses; South Asia -- Ethnic relations -- Congresses